PEMIKIRAN EKONOMI ISLAM MONZER KAHF - Eka Sriwahyuni Sriwahyuni (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2017)
The rationale of MonzerKahf is the Qur'an and Hadith, it is this foundation that makes him offer to the Muslim community so that in the economic activities of the state is restored to the principles of the Qur'an and Hadith. His thinking leads to the achievement of socioeconomic justice and detailed theories ..as for his thoughts focused on zakat in various forms. So that a country has the welfare of society with the fulfillment of life needs